Mulching effect of plant residues of chemically contrasting compositions on soil organic matter content and cation exchange capacity - Tian, G.; Brussaard, Lijbert (Informa UK Limited, 1997)
Effects of five types of plant residues [Acioa, presently Dactyladenia barteri, Gliricidia sepium, and Leucaena lecocephala prunings, maize (Zea mays) stover and rice (Oryza sativa) straw] applied as mulch on soil organic matter (SOM) content and effective cation exchange capacity (ECEC) were studied on an Alfisol in the humid tropics. Plant residue mulch resulted in a decline in SOM and ECEC during two years of cropping following six years of grass fallow. Rice straw mulch resulted in less and maize stover mulch in a greater decrease of SOM and ECEC than the other mulches. Decrease in SOM and ECEC is attributed to the mulching effect on the soil micro‐climate which enhanced the decomposition of SOM accumulated during the grass fallow prior to the initiation of the experiment. In order to maintain SOM for a tropical soil, plant residues with high lignin, polyphenols, and silica will have to be among residue species when applied in continuous cropping systems.